Observing three points - Mallon, Darci (My University, 1993)
This exhibition at the Glenbow Museum comprised seven large artworks: four made with ink on multiple layers of mylar, braced together with steel, suspended and backlit; and three drawn with ink, chalk, and graphite on panels of BFK paper. The subjects, drawn with the artist's inked fingerprints, were small objects, each with a point: a railroad spike, a boat hook and a tack. The development of this body of work was informed by the artist's interest in existentialism and the phenomenology of perception.
Keywords: existentialism; phenomenology; drawing; fingerprints; Sarte\; Merleau-Ponty